ON THE ISSUE OF ORGANIZING THE HIERARCHICAL STRUCTURE OF CONTROL SYSTEMS - Sabirov Ulugbek Kuchkarovich (European Science Publishing, 2024)
The article discusses the organization of the hierarchical structure of control systems. Hierarchy is defined as “verticality”, “multi-stage” and “orderliness” of elements, tasks and processes in the structure of the control system. A hierarchical structure of the control system of a modern manufacturing enterprise is proposed according to the principle of “hierarchy- control methods”.
Keywords: hierarchy, control system, control methods, control principles, verticality, multi-stage, orderliness.